Subgingival Microbiome is Associated with Alveolar Bone Loss Measured 5-Years Later in Postmenopausal Women - LaMonte, Michael J. (J Periodontol, 2020)
BACKGROUND: The aim of this study was to quantify the association between subgingival microbiota and periodontal disease progression in older women, for which limited published data exist. METHODS: A total of 1,016 postmenopausal women, aged 53–81 years, completed baseline (1997–2001) and 5-year (2002–2006) dental exams that included probing depth, clinical attachment level, gingival bleeding, and radiographic alveolar crestal height (ACH). Baseline microbiota were measured in subgingival plaque using 16S rRNA sequencing. Associations between 52 microbiota we previously found statistically significantly associated with clinical periodontal disease at baseline, were examined with disease progression. The traditional Socransky microbiota complexes also were evaluated. Side-by-side radiograph comparisons were used to define progression as ≥2 teeth with ≥1mm ACH loss or ≥1 new tooth loss to periodontitis. The association between baseline centered log(2) ratio transformed microbial relative abundances and 5-year periodontal disease progression was measured with generalized linear models. RESULTS: Of 36 microbiota we previously showed were elevated in moderate/severe disease at baseline, 24 had statistically significantly higher baseline mean relative abundance in progressing compared with non-progressing women (P<.05, all); which included all Socransky red bacteria (P. gingivalis, T. forsythia, T. denticola). Of 16 microbiota elevated in none/mild disease at baseline, 5 had statistically significantly lower baseline abundance in non-progressing compared with progressing women (P<.05, all), including one Socransky yellow bacteria (S. oralis). When adjusted for baseline age, socioeconomic status, and self-rated general health status, odds ratios for 5-year progression ranged from 1.18–1.51 (per 1-standard deviation increment in relative abundance) for microbiota statistically significantly (P<.05) positively associated with progression, and from 0.77–0.82 for those statistically significantly (P<.05) inversely associated with progression. These associations were similar when stratified on baseline levels of pocket depth, gingival bleeding, ACH, and smoking status. CONCLUSIONS: These prospective results affirm clearly that subgingival microbiota are measurably elevated several years prior to progression of alveolar bone loss, and include antecedent elevations in previously undocumented taxa additional to known Socransky pathogenic complexes.